A critical introduction to queer theory - Sullivan, Nikki, 1962- (Edinburgh University Press, 2003)
"Explores how sexuality, subjectivity and sociality have been discursively produced in various historical and cultural contexts. The book begins by putting gay and lesbian sexuality and politics in historical context and demonstrates how, and why, Queer Theory emerged in the West in the late twentieth century. It goes on to provide a detailed overview of the complex ways in which Queer Theory has been practised. Each chapter focuses on an issue or topic, provides a critical analysis of the specific ways in which it has been responded to by critics (including Sigmund Freud, Michel Foucault, Judith Butler, Jacques Derrida, Jean-Luc Nancy, Adrienne Rich and Laura Mulvey), and introduces key terms. Each chapter also discusses contemporary cinematic texts."--